Fatigue analysis of a generic 7.5 MW reference rotor hub - Krishnappa, Likith (2017)
In recent decades, there has been a tremendous increase in the utilization of wind energy to generate electricity. In order to cater to the rising power demand, the capacities of wind turbines are continuously increasing. As the capacity of the wind turbines increase, so does the problems associated with them. To provide solutions to such problems, it is essential to have well documented literature on all components of the wind turbine. There has been a lot of research carried out on some parts of the wind turbine. However, it has been observed that there is inadequate information available on rotor hubs. In this thesis, an effort is made to add literature to the field of fatigue analysis of rotor hub. To accomplish this goal, a generic 7.5MW reference rotor hub is modelled and subjected to extreme load cases followed by the fatigue life cycle analysis by applying the Damage Equivalent Loads (DELs). The design of the model is then optimized using the initial results in order to obtain a rotor hub with minimum size and weight, which is able to withstand the extreme loads and avoid failure due to fatigue for 1 x 10^7 cycles.